Kepercayaan Diri pada Siswa PKBM Berdikari Surakarta Paket A - Afiifah Ramadhani Kusuma (Asosiasi Riset Ilmu Kesehatan Indonesia, 2025)
This research was conducted at PKBM Berdikari Surakarta and focuses on the self-confidence levels of package A students, as self-confidence is very important for the learning process of students, especially at the elementary school level. The self-confidence of students is crucial for their personal and academic progress, influencing their ability to interact with others and develop their own potential. These findings highlight the need for environmental support to enhance students' self-confidence in both academic and social contexts.